Moralische Dimensionen der Verletzlichkeit des Menschen Interdisziplinäre Perspektiven auf einen anthropologischen Grundbegriff und seine Relevanz für die Medizinethik - Coors, Michael (Humanprojekt, 2022)
The anthropological concept of vulnerability has been discussed for some years as an alternative to an autonomy-centred approach to medical ethics. But what exactly is meant by vulnerability and what is its moral relevance remains a controversial question. In a three-year discourse project, the authors of this volume have dealt with the concept of human vulnerability from different perspectives. As a result of this joint discourse, this volume brings together different philosophical, theological and medical ethical perspectives that deal with the anthropological and ethical foundations of the phenomenon of human vulnerability, as well as with its function and relevance for concrete medical ethical questions.